2011
DOI: 10.3109/00952990.2011.596977
|View full text |Cite
|
Sign up to set email alerts
|

NIDA’s Clinical Trials Network: An Opportunity for HIV Research in Community Substance Abuse Treatment Programs

Abstract: Background/Objectives HIV continues to be a significant problem among substance users and their sexual partners in the United States. The National Drug Abuse Treatment Clinical Trials Network (CTN) offers a national platform for effectiveness trials of HIV interventions in community substance abuse treatment programs. This article presents the HIV activities of the CTN during its first 10 years. Results While emphasizing CTN HIV protocols, this article reviews the (1) HIV context for this work; (2) the colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Refusal to share needles could also result in loss of the woman’s source of subsistence and income, and put pressure on her to engage in high-risk behavior [43]. The likelihood of engaging in risky behaviors increases as abuse and dependency on drugs increases [44]. FSWs who use drugs may be more likely to acquiesce to a client’s demands for unprotected sex if they are under the influence of drugs or experiencing withdrawal [4].…”
Section: Multilevel Driversmentioning
confidence: 99%
“…Refusal to share needles could also result in loss of the woman’s source of subsistence and income, and put pressure on her to engage in high-risk behavior [43]. The likelihood of engaging in risky behaviors increases as abuse and dependency on drugs increases [44]. FSWs who use drugs may be more likely to acquiesce to a client’s demands for unprotected sex if they are under the influence of drugs or experiencing withdrawal [4].…”
Section: Multilevel Driversmentioning
confidence: 99%
“…Editorial Both illicit drug abuse and HIV/AIDS are among the most important health concerns globally. During the past decade, HIV has continued to be a major health challenge among drug abusers [1]. There are a large number of studies on drug abuse among HIV positive patients which have shown injection drug use -either directly or indirectly-is responsible for more than one third of HIV infections [2].…”
Section: A Comprehensive Model For Drug Abuse and Hiv/ Aids Health Carementioning
confidence: 99%
“…Since its inception, the CTN has conducted five HIV-specific protocols (Tross et al, 2011). These protocols include geographically diverse programs from across the U.S. and are developed through ongoing partnerships between providers and researchers.…”
Section: Community-based Effectiveness Research: the Nida Ctnmentioning
confidence: 99%